HIPERTENSAO ARTERIAL NA CRIANCA - Dias Bastos, H.; Macedo, C. S.; Riyuso, M. C. (My University, 1992)
The objective of this report was to summarily review the concept and the prevalence of arterial hypertension in children, its peculiarities and the difficulties in measuring of blood pressure at this age. Considerations of clinical picture, diagnosis, laboratory and drug-induced test (Captopril) were discussed. The authors presented various therapies utilized in hypertension and hypertensive crisis.
Arterial hypertension in children
Keywords: amiloride; atenolol; beta adrenergic receptor blocking agent; calcium channel blocking agent; captopril; chlortalidone; clonidine; diazoxide; dipeptidyl carboxypeptidase inhibitor; diuretic agent; enalapril; furosemide; hydralazine; hydrochlorothiazide; labetalol; methyldopa; minoxidil; nifedipine; nitroprusside sodium; phentolamine; prazosin; propranolol; spironolactone; triamterene; arterial pressure; child; human; hypertension; review